PENGEMBANGAN CRITIKAL THINKING MAHASISWA MELALUI PENERAPAN PENDEKATAN INQUIRY PADA MATAKULIAH PENDIDIKAN SAINS - Widowati, Asri (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Critical thinking is an important matter and a vital topic in modern education. This ability is used in so many human life aspects. This ability is seldom be learnt although it is including the part of science. The aim of this research is knowing development critical thinking ability of students through applying inquiry approach at Science Education lecture. Research conducted with qualitative approach and strategy of this research is by simulation observation. Subject of this research is Biological Education students. Data collected by using critical thinking observation sheet. Existence of indication meaningful learning is be expressed from learning process observation and experiment report. Result of research indicate that the aspects of critical thinking can be developed by applying inquiry approach. Some aspects of critical thinking ability can be reached by student with good category, and the other aspects can be reached with good enough.